Design of an IoT-Based Automatic Switching and Monitoring System for Hybrid Power Plants - Aguska, Anggi; Haryudo, Subuh Isnur; Kartini, Unit Three; Rohman, Miftahur (invotek, 2024)
Hybrid power generation, a power plant that combines two or more plants, continues to grow along with technological advances. The performance of these power plants relies heavily on effective switching and monitoring systems. Monitoring data is critical in maintenance scheduling, preventive intervention, and the timely identification and assessment of environmental changes. One of the switching and monitoring technologies integrated with the Internet is the Internet of Things (IoT) technology. This study introduces a system design capable of wirelessly performing switching operations and transmitting real-time data to a hybrid power plant monitoring system through an application. Test results demonstrate that the system successfully executes automatic switching between the hybrid power plant and the PLN electricity grid based on accumulator voltage thresholds. The monitoring data analysis reveals MAPE values of 2.959% and 3.577% for the voltage and current of the hybrid power plant, and a MAPE of 1% for the accumulator voltage. The voltage and load current readings also exhibit MAPEs of 0.604% and 8.625%. Based on the test results, it can be concluded that this device shows the ability of the system to automate the switching of resources to the load and monitor the hybrid power plant very well, with the smallest MAPE value achieved of 0.604%.